Research on an apparatus for separating immiscible liquids - Valeev S. I. (E3S Web of Conferences)
The analysis of publications related to the use of hydrocyclone-type apparatuses in various industries has shown insufficient elaboration of a number of issues in terms of application in the separation of immiscible liquids with a low content of light impurities. Proceeding from it the objective of experimental research on selection of optimal designs of hydrocyclones for cleaning of immiscible liquids of various productions is set. The results of experiments on the selection of the optimal ratio of flow rates through the upper and lower discharge nozzles in a cylindrical hydrocyclone of small diameter are given. Experimental research of velocity fields and pressures in a cylindrical hydrocyclone of not large diameter depending on the ratio of flow rates through the discharge spigots. The obtained results indicate the promising application of hydrocyclones of small diameter for the separation of emulsion-type liquids with a low concentration of light impurities.